2018
DOI: 10.1021/acs.joc.8b01454
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Enantioselective Michael Reactions Catalyzed by a Calixarene-Based Primary Amine Thiourea

Abstract: An upper-rim functionalized calix[4]arene-based thiourea installed onto the ( R, R)-1,2-cyclohexanediamine scaffold was synthesized with a view to investigate its catalytic ability in enantioselective Michael additions. The reactions were found to conveniently proceed under solvent-free conditions, observing good to high enantioselectivities. From this preliminary study, the calix[4]arene unit is likely to play a role in affecting the conversion and to a lesser extent to the stereochemical outcome of the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…A common strategy for the green concept is to use green solvents such as ionic liquid and water to replace organic solvents. However, these green Michael addition reactions are suitable only for soluble/liquid reactants, and not for insoluble/solid reactants.…”
Section: Optimization Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A common strategy for the green concept is to use green solvents such as ionic liquid and water to replace organic solvents. However, these green Michael addition reactions are suitable only for soluble/liquid reactants, and not for insoluble/solid reactants.…”
Section: Optimization Studiesmentioning
confidence: 99%
“…A number of solvent‐free Michael addition reactions have been reported in the literature . However, these reactions often require high temperature,[16a] transition metals as catalysts, and long reaction time from 0.5 h to several days . Therefore, efforts are still needed to improve the reaction conditions of Michael addition reactions for the purpose of future applications, for example, the synthesis of biofuels.…”
Section: Optimization Studiesmentioning
confidence: 99%
“…In 2018, a primary amine based on ( R , R )‐1,2 cyclohexanediamine bearing an upper‐rim fixed calix[4]arene thiourea moiety was synthesized as an effective aminocatalyst in the Michael reaction under solvent‐free conditions . By using catalyst 87 the reaction was also tested in water and chloroform but lower yield and enantioselectivity were obtained.…”
Section: Solvent‐free Reactions In Asymmetric Catalysismentioning
confidence: 99%
“…Chiral cavities are of interest for their potential chiral recognition of racemic guests [3] and chiral catalysis. [4] Our goal is to utilise the chiral cavity of this resorcinarene to enantioselectively bind one enantiomer of a racemic mixture, thus enabling chiral resolution. However, as it is, the cavity of this resorcinarene would not have enough binding interactions for the guest to be retained inside the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In this report, a crown ether was attached to the distal phenolic positions of the narrower rim of p-tert-butylcalixarene, with retention of the cone conformation (Figure 1, left). This pioneering work set the stage for the development of 1,3-alternate calix [4]arene-monocrown-6 derivatives ( Figure 1, right) by the same research group, which were shown to be remarkably selective ionophores for caesium cations. [7] Such was the selectivity of these calixarene crowns that they were used to extract caesium ions for the industrial treatment of nuclear waste.…”
Section: Introductionmentioning
confidence: 99%